Solution of Nonlinear Fractional Differential Equations q-Homotpy Transformation Method - Dubey, Ravi Shanker; Huseen, Shaheed Naser; Goswami, Pranay; Amitkumar, Tailor Gomatiben (Discontinuity, Nonlinearity, and Complexity, 2026)
In this article, q-homotopy analysis transformation method (q-HATM) has been applied to solve fractional partial differential equations. The q-HATM is a well known method, which is the outcome of the conjunction of q- Homotopy analysis method and Laplace transform. Which provides the solution of such problems in a very easy manner. In our analysis, we derive the approximate analytical results of the non-linear fractional differential equation. And it shows that this method is more likely to converge for a series solution.